Call Integration in English Language Teaching into Offline and Online Classes - R. Muhammad Nasrullah; Mutmainnah Mustofa; Imam Wahyudi Karimullah; Suatmo Pantja Putra (Budapest International Research and Critics University, 2022)
The research objective is to analyze call integration in english language teaching into offline and online classes. This study uses a qualitative approach. The population in this study is english college teachers at Universitas Wiraraja, who teach english in between 2019 and 2021 academic year in different faculties. The writer uses a saturated sampling model. All subject participants available, which are four english teachers, are selected to be involved in this study. The type of instruments used in this study is interview to analyze the study questions and divided into two stages: pre-interview and in-depth interview. The results showed that the writer identified two sub-themes of the teachers’ experiences: opportunities and challenges of computer-assisted language learning in english language teaching for offline and online classes. All respondents reflected that it is essential to combine all skills in their teaching practices whether in offline and online classes.